Between pulpit and pew: the supernatural world in Mormon history and folklore - Reeve, W. Paul, editor; Van Wagenen, Michael Scott, editor; Utah State University Press, publisher (Colorado State University. Libraries, 2011)
Mormons gave to supernatural legends and events distinctive meanings related to Mormon theology and culture, but such narratives incorporated motifs found in many cultures. Many such historical legends and beliefs continue to find adherents down to the present. In this collection, historians employ folklore to illuminate the cultural and religious history of the Mormon people.
Between pulpit and pew: where history and lore intersect / W. Paul Reeve and Michael Scott Van Wagenen -- A Mormon bigfoot: David Patten's Cain and the conception of evil in LDS folklore / Matthew Bowman -- "As ugly as evil," and "as wicked as Hell": Gadianton robbers and the legend process among the Mormons / W. Paul Reeve -- Raising the dead: Mormons, evangelicals, and miracles in America / Matthew Bowman -- Singular phenomena: the evolving Mormon interpretation of unidentified flying objects / Michael Scott Van Wagenen -- A currency of faith: taking stock in Utah County's Dream Mine / Kevin Cantera -- A Nessie in Mormon country / Alan L. Morrell -- Walking on water: nineteenth-century prophets and a legend of religious imposture / Stanley J. Thayne.
Keywords: Mormons -- Folklore; Legends -- Utah -- History and criticism; Folklore -- Utah